Rule 15C2-12: A Flawed Regulatory Framework Creates Pitfalls for Municipal Issuers - Lisa M. Fairchild; Nan S. Ellis (Washington University Journal of Law & Policy, 2000)
This article examines the disclosure requirements that issuers face in today’s municipal bond market. Previous attention has focused on the failure of Rule 15c2-12 and its amendments to protect investors, due to its inherent inadequacies. This article explores the implications for issuers of the inadequacy of this regulation. The article argues that the existing system of state, federal and voluntary regulation is inadequate and creates numerous pitfalls for issuers— specifically, that the non-specificity weaknesses of Rule 15c2-12 impose burdens that issuers must overcome. First, this article outlines the regulatory environment of the municipal bond market, and highlights gaps in regulation. Second, this article addresses how disclosure is beneficial to issuers. Third, this article addresses how the inadequate disclosure scheme dictated by Rule 15c2-12 affects issuers. Finally, this article recommends that the bifurcated nature of security regulation, with one scheme imposed on issuers of corporate securities and another imposed on municipal issuers, be abandoned.
Keywords: Disclosure (Securities law); Municipal bonds